Analisis Beberapa Sifat Kimia Tanah Ultisol pada Lahan Kelapa Sawit di Desa Kelompu Kecamatan Kembayan Kabupaten Sanggau - Dinata, Marta; Sulakhudin, Sulakhudin; Agustine, Leony (Soil Science Department, Faculty of Agriculture, Tanjungpura University, 2024)
Oil Palm Plants (Elaeis guineensis Jacq.) are one type of plantation crop that occupies an important position in the agricultural sector in general, and the plantation sector in particular. Oil palm can grow in Ultisol soil which has a low fertility level. The characteristics of the elements in the soil greatly influence the characteristics of the elements in the plants that grow on it, so that the content of essential and non-essential elements that are deficient or excessive in plant tissue will reflect the content of the elements in the soil. The aim of this research is to analyze the nutrients magnesium, calcium and sodium as well as the soil base saturation of ultisol on oil palm land in Kelompu Village, Kembayan District, Sanggau Regency. The method used in this research is the survey method and soil sampling using the grid system method. The observation point represents a land area of 1,000 x 1,000 m or 10 ha. Soil samples or specimens are taken at a depth of 0-30 cm in a composite manner for the purpose of analyzing the chemical properties of the soil. Oil palm fields in Ultisol soil for all locations have almost the same soil chemical properties of magnesium, calcium and sodium, that is, they tend to have chemical properties that are classified as low class.